2018
DOI: 10.1002/jms.4202
|View full text |Cite
|
Sign up to set email alerts
|

Assay of lovastatin containing dietary supplement by LC‐MS/MS under MRM condition

Abstract: Monacolin K, the active ingredient present in dietary supplement, is a nutraceutical whose health benefits have been widely documented. A fast approach for the assay of lovastatin in both forms, lactone and acid, by mass spectrometry is presented. The quantitative assay is carried out by high‐performance liquid chromatography‐tandem mass spectrometry by using the multiple reaction monitoring mode and simvastatin and pravastatin as internal standards. The accuracy values ranged from 97 to 101%; the analytical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As listed in Tables 1 and 2 and shown in Figure 1, the peaks for lovastatin acid, lovastatin, simvastatin acid, simvastatin and mevastatin are close to each other and have similar UV–Vis spectra. The identities of the potential adulterants were confirmed as lovastatin and lovastatin acid (Figure 4) by comparison of the calculated precursor‐product ion ratios with the ion ratio of the standard, thus allowing accurate determination via LC/ESI‐MS/MS 19,25 . As listed in Table 5, 13 dietary supplements (5 tablets, 7 hard capsules, and 1 soft capsule) contained lovastatin acid and lovastatin at concentrations ranging from <LOQ to 4.12 mg/g and <LOQ to 9.65 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As listed in Tables 1 and 2 and shown in Figure 1, the peaks for lovastatin acid, lovastatin, simvastatin acid, simvastatin and mevastatin are close to each other and have similar UV–Vis spectra. The identities of the potential adulterants were confirmed as lovastatin and lovastatin acid (Figure 4) by comparison of the calculated precursor‐product ion ratios with the ion ratio of the standard, thus allowing accurate determination via LC/ESI‐MS/MS 19,25 . As listed in Table 5, 13 dietary supplements (5 tablets, 7 hard capsules, and 1 soft capsule) contained lovastatin acid and lovastatin at concentrations ranging from <LOQ to 4.12 mg/g and <LOQ to 9.65 mg/g, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Guo et al reported an LC/ion trap time‐of‐flight mass spectrometry method for the screening of various drug compounds including five statins and two fibrates in dietary supplements 15 . In addition, Cohen et al reported a method for the determination of lovastatin in dietary supplements using an UPLC system equipped with a diode‐array detector and a quadrupole time‐of‐flight mass spectrometer 16 Recently, Di Donna et al analyzed lovastatin‐containing dietary supplements using LC/tandem mass spectrometry (LC/MS/MS) 19 . In these earlier studies, the statins were analyzed in several groups to which they were assigned by their respective optimal detection wavelength because of the similar spectra of the target compounds at the absorption wavelengths in the UV and visible regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers good detection of monacolin analogs in RYR. Donna et al [68] uses the multiple reaction monitoring (MRM) mode and HPLC-MS/MS as the analytical method: simvastatin and pravastatin were used as indicators to determine the acid and lactone monacolin K content in RYR. Different detectors have different detection ranges.…”
Section: The Detection Methods Of Monacolin K Of Ryrmentioning
confidence: 99%
“…Conventionally, they are analyzed by gas chromatography (GC) or high‐performance liquid chromatography (HPLC) coupled with mass spectrometry (MS), ultraviolet, and electrochemical detection 17–23 . MS is certainly the most appropriate tool for a specific and sensitive analysis 24,25 ; moreover, this technique allows the use of labeled internal standards, which assure a high grade of accuracy in the analysis 26,27 . In this work, we developed a new approach based on the use of paper spray (PS) ionization coupled with tandem MS. PS is an ambient ion source, which allows to create ions directly in their native state, performing fast analysis of a wide variety of compounds present in complex mixtures, with a minimal sample pretreatment and without any chromatographic separation.…”
Section: Introductionmentioning
confidence: 99%